Arthritis, Occupational Class, and the Aging US Workforce - Caban-Martinez, Alberto J. (American Public Health Association, 2011)
Objectives. The working poor sometimes delay retirement to survive. However, their higher risk of disease and disability threatens both their financial survival and their ability to work through the retirement years. We used the burden of disease attributable to arthritis by occupational class to illustrate the challenges faced by the older poor. Methods. We merged data from the National Health Interview Survey, Medical Expenditure Panel Survey, and the National Death Index into a single database. We then calculated and compared age- and occupational class–specific quality-adjusted life years (QALYs) between workers with and without arthritis by using unabridged life tables. Results. White-collar workers have a higher overall health-related quality of life than do other workers, and suffer fewer QALYs lost to arthritis at all ages. For instance, whereas 65-year-old white-collar workers without arthritis look forward to 17 QALYs of future life, blue-collar workers with arthritis experience only 11, and are much less likely to remain in the workforce than are those in service, farming, or white-collar jobs. Conclusions. To meet the needs of the aging workforce, more extensive health and disability insurance will be needed.